2007
DOI: 10.1248/yakushi.127.1731
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Compliance for Oral Medicines with MMSE, Minimental State Examination, in Hospitalized Elderly Patients

Abstract: The minimental state examination (MMSE) is a widely used, standardized method to assess cognitive function including movement-related disorders with high reliability. We studied the relationship between MMSE scores and the ability to take oral medications correctly (ingestion compliance) in 70 elderly inpatients (mean age 71.3±7.0 years). Patients with abnormal glucose tolerance as determined by an HbA 1c level of 5.8% or greater including diabetes showed a trend of lower MMSE scores compared with patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This test showed also some power to detect (sensitivity of 66%) and rule out (specificity of 81%) lack of adherence in this context. A study conducted in Japan found a sensitivity of 75% and a specificity of 81.5% for non-adherence with MM, using 26 as the cut-off point, for patients hospitalized with diabetes and intolerance to glucose [21].…”
Section: Discussionmentioning
confidence: 99%
“…This test showed also some power to detect (sensitivity of 66%) and rule out (specificity of 81%) lack of adherence in this context. A study conducted in Japan found a sensitivity of 75% and a specificity of 81.5% for non-adherence with MM, using 26 as the cut-off point, for patients hospitalized with diabetes and intolerance to glucose [21].…”
Section: Discussionmentioning
confidence: 99%